2015
DOI: 10.18632/oncotarget.4554
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of salivary gland tumors

Abstract: Effective treatment options for advanced salivary gland tumors are lacking. To better understand these tumors, we report their genomic landscape. We studied the molecular aberrations in 117 patients with salivary gland tumors that were, on physician request, tested in a Clinical Laboratory Improvement Amendments (CLIA) laboratory (Foundation Medicine, Cambridge, MA) using next-generation sequencing (182 or 236 genes), and analyzed by N-of-One, Inc. (Lexington, MA). There were 354 total aberrations, with 240 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 50 publications
(62 reference statements)
6
40
0
Order By: Relevance
“…Studies of salivary duct carcinoma reported either HER2 amplification or mutations activating the MAPK pathway in most tumors, with NF1 mutations present in 16% to 17% of cases, suggesting that a subset of patients with salivary duct carcinoma may benefit from mitogen‐activated protein kinase inhibitors. Case 2 harbored both strong p16INK4a expression and CDK4 amplification; the cyclin pathway has been reported to be frequently altered in salivary gland cancer . Interestingly, p16INK4a overexpression is commonly seen in human papillomavirus–induced oropharyngeal squamous cell carcinoma, which presents in younger nonsmokers .…”
Section: Discussionmentioning
confidence: 97%
“…Studies of salivary duct carcinoma reported either HER2 amplification or mutations activating the MAPK pathway in most tumors, with NF1 mutations present in 16% to 17% of cases, suggesting that a subset of patients with salivary duct carcinoma may benefit from mitogen‐activated protein kinase inhibitors. Case 2 harbored both strong p16INK4a expression and CDK4 amplification; the cyclin pathway has been reported to be frequently altered in salivary gland cancer . Interestingly, p16INK4a overexpression is commonly seen in human papillomavirus–induced oropharyngeal squamous cell carcinoma, which presents in younger nonsmokers .…”
Section: Discussionmentioning
confidence: 97%
“…Molecular singletons as the norm are commonly reported in other cancers as well (44)(45)(46)(47)(48). Considering that effective therapies for mesothelioma are lacking (8)(9)(10)(11)(12), clinical trials for mesothelioma that incorporate molecular profiling for patient selection and appropriately customized therapy are warranted (49).…”
Section: Discussionmentioning
confidence: 99%
“…Using next-generation sequencing to study 117 different salivary gland tumors, it was found that the most common aberrations were in the TP53 gene, followed by the cyclin and PI3K pathways. More importantly, 91.5% of these patients had at least one aberration that was potentially targetable by an FDAapproved drug or an investigational agent in a clinical trial, showing that research on targeted therapies based on molecular profiling is worthwhile [81]. A study of 149 patients also had similar results, with further alterations in RAS, ERBB2, NOTCH1, NF1, and RET, showing diverse genetic alterations that may lead to novel treatment options [69].…”
Section: Clinical Relevance Of Heterogeneitymentioning
confidence: 91%